2021
DOI: 10.1289/ehp9321
|View full text |Cite
|
Sign up to set email alerts
|

Key Characteristics of Cardiovascular Toxicants

Abstract: Background: The concept of chemical agents having properties that confer potential hazard called key characteristics (KCs) was first developed to identify carcinogenic hazards. Identification of KCs of cardiovascular (CV) toxicants could facilitate the systematic assessment of CV hazards and understanding of assay and data gaps associated with current approaches. Objectives: We sought to develop a consensus-based synthesis of scientific evidence on the KCs of chemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 373 publications
(273 reference statements)
1
32
0
Order By: Relevance
“…[14] Cytotoxicity and in ammation in cardiac tissue are critical events in CVD initiation and progression. [14][15][16][17] Furthermore, studies have indicated that water-soluble components in PM 2.5 could activate reactive oxygen species (ROS) and release in ammatory cytokines on airway epithelial cells. [18] While the literature on different PM 2.5 induces myocardial brosis is growing, it is unknown whether the PM 2.5 components at critical concentrations can target to in uence the occurrence of myocardial brosis.…”
mentioning
confidence: 99%
“…[14] Cytotoxicity and in ammation in cardiac tissue are critical events in CVD initiation and progression. [14][15][16][17] Furthermore, studies have indicated that water-soluble components in PM 2.5 could activate reactive oxygen species (ROS) and release in ammatory cytokines on airway epithelial cells. [18] While the literature on different PM 2.5 induces myocardial brosis is growing, it is unknown whether the PM 2.5 components at critical concentrations can target to in uence the occurrence of myocardial brosis.…”
mentioning
confidence: 99%
“… 5 , 6 The authors of a commentary recently published in Environmental Health Perspectives extend this work to chemicals with cardiovascular toxicity. 7 …”
mentioning
confidence: 99%
“…Abnormal ion channel activity can lead to cardiac arrhythmias and sudden cardiac death. 7 Antiarrhythmic drugs 8 and the environmental chemical bisphenol A 9 are example compounds with KC1.…”
mentioning
confidence: 99%
See 2 more Smart Citations